PENGARUH PENGGUNAAN MEDIA SOSIAL DAN ISI PESAN TERHADAP MOTIVASI BERPRESTASI MENGIKUTI BEASISWA (Survei Pada Followers @scholarship4us) - Mutiara Putri (2023)
The purpose of this study was to examine the effect of using Instagram social media and message content on the @scholarship4us Instagram account on followers' achievement motivation. The background of this research is that the researcher wants to know whether there is an effect of the use of social media and message content on the achievement motivation of @scholarship4us followers participating in scholarships. The theory used to explain this research is the theory of Media Dependence (Dependency Theory). This study used a quantitative explanatory approach with a survey method in the form of a Google Form questionnaire which was distributed to 100 respondents following the Instagram account @scholarship4us. The sampling technique used is the Purposive Sampling technique using the Taro Yamane formula and a precision value of 10%. This study takes data sources from primary data. Through the results of hypothesis testing with the T test, the result is that the T count is 2.952 and the T table value is 1.985, which means that T count > T table is 2.952 > 1.985. So it can be concluded that the variable use of social media and message content has a significant influence on followers' achievement motivation. Based on the results of the coefficient of determination test, it was found that the amount of Instagram social media use and message content on the @scholarship4us Instagram account on followers' achievement motivation was 55.4% and the remaining 44.6% was influenced by other factors not examined in this study. This shows that the use of social media and the contents of messages on the Instagram account @scholarship4us have an important role in fulfilling achievement motivation to follow the followers @scholarship4us scholarship.